Transport services of Malaysia Airlines: a study on the service level performance of the transport services for airlines crew / Wan Mohamad Nasle Wan Mohamad Nasir - Wan Mohamad Nasir, Wan Mohamad Nasle (1997)
The main purpose of this study are to identify the service level performance of Transport Services for Malaysia Airlines crew and also to finds ways of improving the service level for this service. As for this study, it will concentrate on the service level position for both cabin and technical crew. This is due to the fact that any delay in bringing them to the airport will affect the aircraft departure time and even whole related operation. The data and information for this study are gathered through interviews, observation and other secondary services such as books, magazine and company transport manual outlet. Tables, graphs, pie charts are used to analyze the data. The service level provided by the Transport Services of Malaysia Airlines is still not satisfied their customer. There is lot of room for improvement, the study makes a few recommendations to improve the service.